Pediatric Laser Dentistry : a User`s Guide - Benedicenti, Stefano; Featherstone, John D. B.; Margolis, Fred S.; Caprioglio, Claudia; Genovese, Maria Daniela; Margolis, Fred S.; Olivi, Giovanni (Quintessence, 2011)
This comprehensive text, the first to focus on laser applications in pediatric dentistry, reviews the fundamental principles of laser energy and demonstratesthe essential therapeutic steps of laser radiation in conservative pediatric dentistry. Detailed explanations of the unique interactions of laser radiation with dental tissues—with a focus on the differences speci! c toprimary and young permanent teeth—help clinicians take advantage of themany inherent bene! ts of laser energy, such as selective removal of carious tissue, preservation of healthy mineral structure, disinfection of prepared surfaces, excellent hemostasis, and improved patient comfort and compliance.The predictable clinical protocols for hard and soft tissue application sare detailed step by step with explanations on technique and suggested laser parameters, and the outcomes are illustrated in multiple case studies. Inaddition, the text is rounded out with presentations on innovative therapiesinvolved in laser caries detection, laser irradiation for caries prevention,enamel and dentin laser conditioning, laser radiation for root canal debridingand cleansing, and low-level laser therapy as well as an appendix on laser safety and a glossary of laser terms. This practical guide will inspire pediatricdentists who are new to the laser as well as those experienced in providing laser therapy to adults.